Potensi UEK-SP Kelurahan Rimba Sekampung Untuk Transformasi Menjadi Lembaga Keuangan Mikro (LKM) Di Kota Dumai - Hildawati Hildawati; Dia Meirina Suri (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2020)
According to Law Number 1 of 2013 concerning Microfinance Institutions in article 5, it discusses all activities that collect and distribute funds must be incorporated, be PT or Cooperative. Until now there are still many Microfinance Institutions (LKM) that do not yet have a legal entity such as receiving UEK-SP Raimba Sekampung. This can trigger the risk of bad credit and also default, so that it can hamper the development of the LKM in achieving its goals. This study describes the opportunities and weaknesses and opportunities in the UEK-SP Kelurahan Rimba Sekampung. In addition, this study also describes the direction of the UEK-SP of Kelurahan Rimba Sekampung based on Law no. 1 of 2013. This research is a descriptive study with data collection techniques in the form of interviews and questionnaires. The selection of informants uses a purposive technique. Analysis of technical data used is qualitative and quantitative using SWOT. The results showed that the UEK-SP of Kelurahan Rimba Sekampung was in Quadrant 1 of the SWOT Diagram which could be interpreted that the UEK-SP of Kelurahan Rimba Sekampung could carry out Growth Strategies related to strengths greater than existing and Opportunities greater than needed. In other words, UEK-SP of Kelurahan Rimba Sekampung is designed to be developed into an LKM with clear legality.